Hegemonisk maskulinitet - genbesøgt - Bjerg, Helle (Kvinder, Køn & Forskning, 2015)
Hegemonic masculinity revisited. The analysis unfolds an analytical perspective on affect and intensity based on the conceptualisations of Brian Massumi. It is argued that the analytical conceptualisation of affect, intensity, capacitation and potential offers new analytical and critical perspectives to the analysis of subjectification and intersectionality. The argument is unfolded through an analytical example on the construction of hegemonic masculinity within the lived life of schooling.